Fiscal stimulus and systematic monetary policy: postwar evidence for the United States - Rüth, Sebastian (Economics letters, 2018)
I provide structural VAR evidence that U.S. fiscal stimulus programs induce a systematic loosening of interest rates outside of zero-lower-bound episodes. I characterize this policy easing by the Fed as an indirect reaction to disinflationary dynamics unleashed by fiscal stimulus—a finding I corroborate via Taylor-rule estimations. The supporting monetary policy stance amplifies the impact of the expansion in public spending on GDP by roughly one-third. My evidence aligns with fiscal policy models featuring deep-habits in consumption. The empirical regularity of accommodating policy rates, moreover, questions the perception of stimulus being more effective when policy rates are stuck at zero.